Symbolic Interactionism in Youth Mosque Communication Practices: A Study of Jami’ Mosque Youth Community in Dalu Sepuluh A Village - Evi Sakdiah; Sahlaya, Muhammad Rishan (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Abstrak Penelitian ini bertujuan untuk menganalisis praktik komunikasi dalam kepengurusan Kelompok Remaja Masjid Jami’ Desa Dalu Sepuluh A dengan menggunakan pendekatan teori Interaksionisme Simbolik. Fokus utama penelitian ini adalah bagaimana simbol, bahasa, dan interaksi yang terbentuk dalam aktivitas organisasi remaja masjid memproduksi makna bersama serta membentuk identitas kolektif berbasis nilai keislaman. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data meliputi wawancara mendalam, observasi partisipatif, dan dokumentasi kegiatan organisasi. Hasil penelitian menunjukkan bahwa praktik komunikasi dalam kelompok tidak hanya berfungsi sebagai sarana penyampaian informasi, tetapi juga sarat dengan makna simbolik yang mencerminkan nilai keagamaan, struktur sosial, dan kohesi kelompok. Simbol-simbol seperti salam, penugasan dalam kegiatan dakwah, pemilihan bahasa dalam rapat, dan struktur kepemimpinan berperan sebagai konstruksi simbolik yang memperkuat identitas dan budaya organisasi. Temuan ini memberikan kontribusi terhadap pengembangan kajian komunikasi organisasi keagamaan berbasis komunitas lokal. Kata Kunci: Interaksionisme Simbolik, Komunikasi Organisasi, Remaja Masjid, Makna Simbolik, Komunitas Keagamaan Abstract This study aims to analyze communication practices within the management of the Youth Group of Jami’ Mosque in Dalu Sepuluh A Village through the perspective of Symbolic Interactionism. The primary focus of this research is on how symbols, language, and interaction formed in youth mosque organizational activities produce shared meanings and construct a collective identity grounded in Islamic values. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, participant observation, and documentation of organizational activities. The findings reveal that communication practices within the group do not merely function as channels for information delivery but are rich in symbolic meanings that reflect religious values, social structures, and group cohesion. Symbols such as salam, delegated roles in dakwah activities, language choices in meetings, and religiously oriented leadership structures serve as symbolic constructions that strengthen organizational identity and culture. These findings contribute to the development of organizational communication studies within local-based religious communities. Keywords: Symbolic Interactionism; Organizational Communication; Mosque Youth; Symbolic Meaning; Religious Community